Medicare Part D and the Nursing Home Setting - Stevenson, David G. (2008)
PURPOSE: To explore how Medicare Part D's introduction is changing the operations of long-term care pharmacies (LTCPs) and nursing homes, as well as implications of those changes for nursing home residents. DESIGN AND METHODS: We reviewed existing sources of information and interviewed stakeholders across various perspectives. Thirty-one semi-structured, telephone interviews were conducted with key stakeholders between November 2006 and January 2007. RESULTS: Part D represents a substantial departure from how prescription drugs were previously financed and administered in nursing homes, and nursing home providers and LTCPs have struggled in adapting to some of these changes. Part D increased the variation around formularies and drug management processes for residents at the facility level, creating additional burden on clinical and pharmacy staff and introducing a tension between facilities' need to dispense medications quickly and assuring coverage for those drugs. Nursing home and LTCP stakeholders perceive wide variation across Part D plans in their ability to meet the needs of nursing home residents. IMPLICATIONS: Although LTCPs, nursing homes and their clinicians, and Part D plans will gain experience with the benefit in the nursing home setting over time, stakeholders we interviewed identified a range of longer-term issues and questions that merit attention as the benefit proceeds.